ANALGESIC EFFECTIVENESS OF CONTINUOUS INTERSCALENE CATHETER USE FOR AMBULATORY SHOULDER SURGERY IN PEDIATRIC AND ADOLESCENT PATIENTS. Issue 3 (31st March 2019) - Holland, Erica; Low, Daniel K.; Saper, Michael
BACKGROUND: Continuous interscalene catheters are utilized for inpatient and outpatient postoperative pain control after shoulder surgery. Although prior studies have primarily been limited to adult populations, benefits of peripheral nerve catheters in ambulatory surgical centers have been shown to reduce post operative pain scores, opioid requirements, and post operative nausea. However, their use in a solely pediatric ambulatory setting has not been investigated. The purpose of this study was to retrospectively review the adverse events, analgesic effectiveness, and opioid use after continuous interscalene catheters for ambulatory shoulder surgery in pediatric and adolescent patients. METHODS: A retrospective review was performed of 15 pediatric and adolescent patients (4 female, 11 male), mean age 16 years (range, 12-18 years), and mean weight 78.3 kg (range 53-130 kg), who underwent ultrasound-guided interscalene catheter placement for outpatient shoulder surgery from April 2017 through May 2018. All but one surgery were performed at a dedicated pediatric ambulatory surgery center. Catheters were initially dosed with 0.5% ropivacaine (n = 13) or 0.2% ropivacaine (n = 2) at volumes of 0.1-0.2ml/kg (total, 6-20 ml). By the conclusion of surgery, all catheters were continuously infusing 0.2% ropivacaine at 3-6ml/hr with the majority (n = 10) at 4ml/hr via elastomeric pumps. Time for catheter placement, intraoperative and postoperative intravenous opioids, post-anesthesia recovery unit (PACU) length of stay (LOS), PACU maximum pain scores and rescue medications for post-operative nausea and vomiting (PONV) were recorded. After discharge, all patients received multimodal analgesia (ibuprofen, acetaminophen, and rescue oxycodone). Patients were assessed on postoperative days (POD) 1-3 for numerical rating pain scores (0-10) at rest and with movement, supplemental oxycodone use in the past 24 hours, satisfaction, and adverse effects of treatment. RESULTS: Catheter placement was 100% successful; no procedure had to be aborted during placement because of inability to place catheter. The average time for catheter placement was 11.8 minutes (range, 3-19 minutes). There were 3 adverse events, including one accidental catheter removal in PACU, one dressing failure requiring removal of catheter on POD 2, and one case of Horner's Syndrome. There were no signs of infection, local anesthetic toxicity, or shortness of breath described in any patients. Short acting opioids (Alfentanil and Fentanyl) were used intraoperatively in all but 2 patients, with average dose of 8.5mcg/kg Alfentanil and 0.7mcg/kg Fentanyl. Two patients received long-acting opioids intraoperatively. The mean PACU maximum pain score was 1.4 (range, 0-9). Only 3 patients received rescue intravenous morphine in the PACU with a mean dose of 0.035mg/kg. Mean PACU LOS was 112 minutes (range, 85 – 210 minutes). No patients required any rescue PONV medications in the PACU. Mean pain scores for POD 1- 3 at rest were 2.1, 2.3, and 2.6, respectively; scores with movement were 3.6, 3, and 4.4, respectively. Mean doses (i.e., times of administration) of oxycodone on POD 1-3 respectively were 1.5, 1.3 and 0.5 (range 0-5 doses). All but one patient was very satisfied and would have the catheter placed again. CONCLUSIONS: Outpatient use of continuous interscalene catheters in pediatric and adolescent patients provides excellent intraoperative and early postoperative analgesia during and following shoulder surgery. Their routine use should be considered as they minimize perioperative opioid use with minimal adverse events, adding only small delay to surgical time.